Financial Performance of Islamic Banks: A Comparative Analysis Before and During The COVID-19 Pandemic - Pahlifi, Resa; Yanti, Dharma; Norvadewi (Jurnal Ilmu Ekonomi Terapan, 2023)
The protracted pandemic has an impact on the Islamic banking industry. Comparing the financial performance of Islamic financing before and during the COVID-19 outbreak helped to evaluate the impact of this factor. This type of quantitative research utilizes secondary data in the form of monthly financial reports from the Financial Services Authority's website for 2018–2021. The variables used are ROA, FDR, BOPO, NPF, and CAR. Before and throughout the COVID-19 epidemic, Islamic banks demonstrated varied financial performance levels as measured by the ratios of ROA, FDR, BOPO, and CAR. ROA and CAR ratios have risen throughout the COVID-19 epidemic. During the COVID-19 pandemic, the FDR, BOPO, and NPF ratios declined. The ratio of BOPO to CAR is the finest and most consistent of these five ratios, ranking first (very healthy) before and during the pandemic. The ROA ratio for FDR and NPF remains standard, with an average ranking of second (healthy). The bank's condition stayed normal and healthy over the 2018–2021 period, both before and after the COVID–19 epidemic, despite variations in the financial performance of Islamic banks as indicated by the ROA, FDR, BOPO, NPF, and CAR ratios.